Seleção de genótipos de soja para ampla adaptabilidade e alta estabilidade fenotípica - Oliveira, Valécia Martins de (2014)
Soybean is a central culture whose grain productivity stands out thanks to advances in genetic improvement. The aims recommended to soybean improvement include reaching high grain productivity, stability and adaptability to diverse environments. The research this study presents aimed at studying genotype environment interaction in regard to grain productivity feature, assessing seven soybean genotypes adaptability and phenotypic stability, and selecting lineages of high productivity, adaptability and stability. Five early-cycle soybean lineages developed by Universidade Federal de Uberlândia s genetic improvement program and two testimonies (UFUS Guarani and M-SOY6101) were evaluated. The evaluation took place in seven environments located in the states of Goiás (Palmeiras de Goiás during 2011/12 and 2012/13 harvests; in Urutaí during 2010/11 and 2011/12 harvests; and in Goiatuba during 2011/12 harvests) and Bahia (in Luís Eduardo Magalhães during 2011/12 and 2012/13 harvests). Experiments were designed as random full blocks with three replications. Each unity was made of five rows of soy plant; and each row was five-meter long with a half-meter long space between them. It was taken as useful parcel two central rows minus a halfmeter long cut at their extremities. The character studied was grain productivity, which was measured in kilos per hectare. Methodologies for the analysis of adaptability and stability included both Eberhart and Russel (1966) and Lin and Binns (1988), as modified by Carneiro (1998), besides AMMI analysis. During the experiments the average grain productivity reached 2,739.26 kilos per hectare. Conjoint variance analysis results reveal relevant effects as to genotype environment interaction in connection with grain productivity feature. This result justifies the study of such interaction and grain productivity, which was considered mostly as being of the complex type. L01V13 genotype and UFUS Guarani cultivar showed great adaptation when considered in the light of the methodology of Eberhart and Russel (1966) and the methodology of Lin and Binns (1988) as modified by Carneiro (1998). UFUS cultivar presented high stability in the AMMI analysis. For the most part these methodologies are complementary. When applied as a set, they may increase reliability in the classification and indication of soybean cultivars for certain environments.